Modernization and the Contemporary Sport Stadium - Benjamin Downs; chad seifried (Journal of Applied Sports Management, 2023)
The authors add to the conversation about sport facility construction by discussing the U.S. political economy that led to the contemporary standing of sport facilities. They use modernization theory as a lens or sample guide for sport facility managers to consider when attempting to position their facilities to maximize profits while satisfying consumers and partners.
Keywords: Governance; Policy; Management; Renovation; Sport Facility